Community Liaison as Factor for Image and Positioning of the Autonomous University of Baja California, Mexico, in the Social and Productive Context - Víctor Manuel Alcántar Enríquez; José Luis Arcos Vega (Universidad Autónoma de Baja California, 2009)
This study presents the results of an extensive research on the society's perceptions of the activities the Autonomous University of Baja California (UABC, for its acronym in Spanish Universidad Autónoma de Baja California) develops in Mexico. This non-experimental research uses an explorative-descriptive methodology, with a transactional research design based on a holistic method and an illuminative evaluation, which analyzes the institutional positioning of UABC in several social sectors, as well as its determining factors. Results support the hypothesis that liaison activities have a significant effect on the regional positioning of the UABC as a higher education institution. The results also helped to identify weaknesses and opportunities that could direct future institutional efforts. In addition, this study provides new elements on liaison, institutional image, and positioning, as well as a conceptual model that involves these variables.